Neonatal Adrenal Hemorrhage Associated with Scrotal Hematoma: An Unusual Case Report and Literature Review - Li-Jen Lai; Li-Mien Chen; Po-Yu Chu; Min-Hua Tseng; Chen-Chu Chang; Chien-Wei Lu (Elsevier, 2012)
Neonatal adrenal hemorrhage (NAH) is rare and is found in only 0.2% of newborns. Scrotal hematoma (SH) in newborns is also rare. NAH associated with SH is extremely rare, with only 29 cases reported in the literature. Herein, we report a baby boy who presented with SH; after ultrasonography examinations, the diagnosis of NAH associated with SH was made. He received conservative treatment only. From our experience and that of others, appropriate integration of clinical information, physical examination and the results of abdominal and scrotal ultrasonography can achieve the accurate diagnosis of NAH associated with SH. This association allows conservative treatment that avoids unnecessary surgical exploration.